Evaluation of Sequential Processing for the Extraction of Starch, Lipids, and Proteins From Wheat Bran - Sardari, Roya R. R.; Sutiono, Samuel; Azeem, Hafiz Abdul; Galbe, Mats; Larsson, Mats; Turner, Charlotta; Nordberg Karlsson, Eva (Frontiers in Bioengineering and Biotechnology, 2019)
In line with the need to better utilize agricultural resources, and valorize underutilized fractions, we have developed protocols to increase the use of wheat bran, to improve utilization of this resource to additional products. Here, we report sequential processing for extraction of starch, lipids, and proteins from wheat brans with two different particle sizes leaving a rest-material enriched in dietary fiber. Mild water-based extraction of starch resulted in maximum 81.7 ± 0.67% yield. Supercritical fluid extraction of lipids by CO2 resulted in 55.2 ± 2.4% yield. This was lower than the corresponding yield using Soxhlet extraction, which was used as a reference method, but allowed a continued extraction sequence without denaturation of the proteins remaining in the raw-material. Alkaline extraction of non-degraded proteins resulted in a yield corresponding to one third of the total protein in the material, which was improved to reach 62 ± 8% by a combination of wheat bran enzymes activation followed by Osborne fractionation. The remaining proteins were extracted in degraded form, resulting in maximum 91.6 ± 1.6% yield of the total proteins content. The remaining material in both fine and coarse bran had a fiber content that on average corresponded to 73 ± 3 %. The current work allows separation of several compounds, which is enabling valorization of the bran raw-material into several products.